EFFECT OF EXPERIMENTAL INFECTION WITH Theleria lestoqurdi ON SOME HAEMATOLOGICAL AND BIOCHEMICAL PARAMETERS IN DESTERT EWES DURING PREGNANCY` - Aisha; Elmansoury, A. Elsadig; V, Y.; M.Elbasheir, Husna; M.B.,Elhussein, r;Saad; M, A.; E.A, Babeker (Journal of Veterinary Medicine and Animal Production, 2022)
This study was designed to investigate the effects of experimental infection with Theileria lestoquardi on some biochemical and haematological pictures in Desert ewes during pregnancy. Twenty Sudanese desert ewes were divided equally into two groups of ten each. The first group(A) received infection with T. lestoquardi, while the second group(B) remained as an uninfected control. The estrous of the two groups were synchronized and allowed to mate. Some haematological and biochemical parameters were determined throughout the pregnancy period and compared in both group. The mean values of Hb, PCV,WBCs, serum total proteins, serum albumin and serum globulins were significantly (P<0.05) lower in the infected ewes(A) compared to the control ones(B). However, serum creatinine and serum urea were significantly higher (P<0.05) in the infected group(A) than in the control ones(B) thus reflecting the direct adverse effects of theileria infection.